2022
DOI: 10.1002/bco2.158
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care for non‐metastatic castration‐resistant prostate cancer: A population‐based study

Abstract: Objectives To describe patterns of practice of PSA testing and imaging for Ontario men receiving continuous ADT for the treatment of non‐metastatic castration‐resistant prostate cancer (nmCRPC). Patients and Methods This was a retrospective, longitudinal, population‐based study of administrative health data from 2008 to 2019. Men 65 years and older receiving continuous androgen deprivation therapy (ADT) with documented CRPC were included. An administrative proxy definition was applied to capture patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Treatment was stopped in cases of radiographic progression as per PCWG3 criteria, and investigators were discouraged from changing treatment based solely on rising PSA. In a population-based, patterns-of-care study in nmCRPC, investigators reported that PSA testing and imaging studies were underutilized in real-world settings [52]. The APCCC 2022 panel voted on questions related to how best to use imaging for treatment monitoring in patients with nmCRPC, and when to change treatment.…”
Section: (No Consensus For Any Given Answer Option)mentioning
confidence: 99%
“…Treatment was stopped in cases of radiographic progression as per PCWG3 criteria, and investigators were discouraged from changing treatment based solely on rising PSA. In a population-based, patterns-of-care study in nmCRPC, investigators reported that PSA testing and imaging studies were underutilized in real-world settings [52]. The APCCC 2022 panel voted on questions related to how best to use imaging for treatment monitoring in patients with nmCRPC, and when to change treatment.…”
Section: (No Consensus For Any Given Answer Option)mentioning
confidence: 99%
“…This study’s strengths include the large demographically representative patient population and its context within an equal-access health care system. Most community setting evidence on nmCRPC comes from studies outside the US 54 , 55 , 56 , 57 ; the few US-based studies have focused on patients treated with apalutamide, and thus may not represent all patients with nmCRPC, but only those with high-risk disease. 58 , 59 , 60 Evidence from clinical trials is also subject to the latter weakness, in addition to underrepresenting patients who identify as racial and/or ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, regular PSA monitoring allows the accurate calculation of PSADT, crucial for prognostic risk assessment in nmCRPC and for making evidence-based decisions toward therapy intensification through the addition of ARIs to the treatment backbone, delaying the development of metastases and improving survival ( 53 , 54 , 58 ). In a recent retrospective study, among 944 nmCRPC patients, 97.6% progressed to high-risk disease with PSADT ≤10 months ( 33 ), highlighting the relevance of this biomarker in the identification of the high-risk nmCRPC state.…”
Section: Timely Identification Of Nmcrpc Patients With High Risk Of M...mentioning
confidence: 99%
“…Guidelines recommend PSA testing every 3–4 months and imaging assessment every 3–6 months for patients with PSADT ≤ 10 months and every 6–12 months for those with PSADT >10 months ( 32 ). Despite these recommendations, PSA and imaging assessment are underused in the real-world practice after initiation of continuous ADT, as shown in a large, population-based cohort study where more than half of patients with CRPC who progressed to high-risk nmCRPC received ≤2 PSA tests in the previous year and 31% received no imaging studies in the following 12 months ( 33 ). Infrequent patient monitoring hinders proper disease staging, risk stratification, and detection of treatment failure and/or metastases, with suboptimal patient outcomes.…”
Section: Introductionmentioning
confidence: 99%